Polyglycidol-based metal adhesion promoters. Issue 5 (2nd December 2014) - Koehler, J.; Kuehne, A. J. C.; Piermattei, A.; Qiu, J.; Keul, H. A.; Dirks, T.; Keul, H.; Moeller, M.
Abstract : Hydrophilic adhesion promoters based on polyglycidols bearing phosphonic acid and acrylate moieties are important for biomedical compatibilization of metal implants and catheters. Abstract : Hydrophilic adhesion promoters that facilitate intimate binding between metals and polymers are an important class of materials with a wide variety of applications in biomedical coatings. Currently, non-poly(meth-)acrylate based hydrophilic polymeric adhesives are unavailable. Here, we report the preparation of such adhesion-promoters based on linear polyglycidol for biomedical applications. The adhesion promoting polymer is prepared from partly phosphonoethylated polyglycidol in three steps. First, the remaining hydroxyl groups of the polyglycidol backbone are reacted with acryloyl chloride; secondly, the phosphonate groups are chemoselectively dealkylated using bromotrimethylsilane. Finally, the bis(trimethylsilyl)phosphonate intermediate is converted to the phosphonic acid through ethanolysis. The reaction conditions of each synthetic step are optimized individually and the products are characterized by 1 H, 31 P NMR and SEC analysis. The optimized reaction conditions are applied to establish a straightforward one-pot reaction, resulting in an ethanolic formulation of the adhesion promoter, which can be used immediately for the coating application. Special attention is paid to the stability of the intermediates, the chemoselectivity of the reactions and the shelf-life of the product. 1 H NMR spectroscopy reveals hydrolytic instability of the product under ambient conditions; however, the polymers are sufficiently stable in dry ethanol for at least 14 days. The combination of this hydrophilic polymer with acrylate and phosphonic acid groups constitutes a versatile platform technology for the preparation of thin primer coatings on metal substrates for biomedical applications. The phosphonic acid residues assure strong binding to stainless steel wires and the acrylates can be addressed by UV light to enable crosslinking, thus improving mechanical stability and adhesion between the substrate and a biomedical hydrogel coating. The quality of the adhesion promotion to stainless steel wires is verified by using a lubricious, hydrogel top coat and by evaluating friction and wear resistance of this total coating system. Constant values for friction and wear are obtained, proving the applicability of phosphonic acid-functionalized polyglycidols as metal adhesion promoters for biomedical applications.